Public knowledge about white-collar crime: an exploratory study - Michel, Cedric (Crime, law and social change, 2016)
A growing body of research has revealed that the financial cost and physical harmfulness of white-collar crime overshadow the impact of street crime on society. To date, scholarly efforts that have investigated societal response to crimes of the powerful have limited their field of inquiry to public opinions about white-collar crime. Although these studies have provided valuable empirical evidence of a growing concern among U.S. citizens regarding the danger posed by elite offenses, their failure to include a valid measure of lay knowledge about white-collar crime significantly limits our ability to infer the extent to which the public is familiar with the scope and magnitude of this social issue. The present study seeks to address such limitations by providing the first measure of public knowledge about white-collar crime. Four hundred and eight participants completed an online questionnaire that measured their knowledge about white-collar crime. Results revealed that participants were not sufficiently informed about it and suggest the existence of popular "myths" about crimes of the powerful. These findings have important implications insofar as white-collar crime awareness programs are concerned. Hypothetically, public demand for tougher sanctions against high-status offenders could result from exposure to relevant information about white-collar crime. Nevertheless, "myth" adherence might also undermine the effect of increased awareness on prosecutorial efforts against upper-class criminality.